Updates in Adjuvant Therapy in Pancreatic Cancer: Gemcitabine and Beyond - Richter, Joshua; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
Pancreatic cancer represents the 4th leading cause of cancer deaths in the United States. Surgical resection remains the only potential curative approach. However, given the notion of a high recurrence rate, adjuvant therapy is needed to offset this risk. The 2010 American Society of Oncology Gastrointestinal Cancers Symposium offered new insights into optimized approaches towards adjuvant therapy of pancreatic cancer. Abstracts focusing on the role of targeted therapy utilizing erlotinib or GI-4000 in combination with gemcitabine (Abstracts #224 and #229) were presented. Subbiah, et al. presented a retrospective analysis comparing systemic chemotherapy versus chemoradiotherapy (Abstract #230) in the adjuvant setting. In addition, a data driven prediction tool to help predict which patients would be able to complete a course of adjuvant therapy in order to select out those who may alternative approaches (Abstract #236) was also presented. The authors summarize these findings presented at the 2010 ASCO Gastrointestinal Cancers Symposium, January 22-24, 2010, Orlando, FL, USA. Image: Chemical structure of gemcitabine (Author: Calvero, Wikimedia Comons)